2020
DOI: 10.1590/1806-9282.66.10.1449
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Diseases and diet: an integrative review

Abstract: SUMMARY OBJECTIVE: To gather scientific evidence on the role of diet in inflammatory bowel diseases. METHODS: Integrative review with studies published in the last 10 years in national and international journals. Original studies developed with adult human beings aged ≥18 years were included and articles published before 2010, literature reviews, and those that did not focus on elements that answered the guiding question were excluded. RESULTS: 14 articles were selected that addressed important dietary elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Diet can regulate the systemic inflammation level through pro-inflammatory or anti-inflammatory mechanisms of foods, nutrients and dietary patterns (29,30) . Studies have shown that higher adherence to the Mediterranean diet was significantly associated with lower levels of inflammation, including reduced levels of CRP (C-Reactive Protein) IL-6 and fibrinogen (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Diet can regulate the systemic inflammation level through pro-inflammatory or anti-inflammatory mechanisms of foods, nutrients and dietary patterns (29,30) . Studies have shown that higher adherence to the Mediterranean diet was significantly associated with lower levels of inflammation, including reduced levels of CRP (C-Reactive Protein) IL-6 and fibrinogen (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, a review of the association between inflammatory bowel diseases and diet found that supplementation with soy proteins modulated body fat composition, thus leading to the control of intestinal irritation [117]. In line with this, a recent meta-analysis of randomized control trials (RCTs) examined serum inflammatory markers in postmenopausal women showed evidence of a correlation between soy protein intake and reduced C-reactive protein levels [118].…”
Section: Soy-based Fermented Foodsmentioning
confidence: 90%
“…The effect of milk on IBD is uncertain. Several studies found that milk exacerbated the gastrointestinal symptoms of IBD, [8,21] while other studies noted that milk significantly reduced the risk of IBD. [4,6] These controversial conclusions from previous observational studies could be caused by differences in the type of milk used.…”
Section: Discussionmentioning
confidence: 99%